Characteristics of hybrid composites of coconut coir and arenga fibers on the alkalization process using NaOH - Hesti Istiqlaliyah (BKS-TM Indonesia, 2025)
The use of composite materials has been growing rapidly, particularly for natural fiber-reinforced composites, due to their environmentally friendly properties. This study aims to investigate the characteristics of hybrid composites based on coconut coir and arenga fibers subjected to an alkalization treatment using sodium hydroxide (NaOH) with concentrations of 5% and 10% and immersion times of 2 hours and 6 hours. The alkali treatment was carried out to improve fiber tensile strength by removing hemicellulose, lignin, and impurities from the fiber surface, thereby enhancing interfacial bonding with the polymer matrix. The results showed that fibers treated with 10% NaOH for 2 hours achieved the highest tensile strength of 62.30 MPa, compared to untreated fibers with 38.26 MPa. The fibers with the highest strength were then fabricated into composites with a volume fraction of 30% fiber and 70% matrix, consisting of a 50:50 ratio of coconut coir and arenga fibers. The hybrid composite exhibited a tensile strength of 1146 MPa, while the untreated composite had 198,43 MPa. Based on the tensile test results of both single fibers and composites, it can be concluded that alkali treatment significantly improves the tensile strength of the material.